2008
DOI: 10.1111/j.1469-8137.2008.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of stomatal numbers to CO2 and humidity: control by transpiration rate and abscisic acid

Abstract: Summary• The observation that stomatal density (number mm −2 ) on herbarium leaves had decreased over the last century represents clear evidence that plants have responded to anthropogenic increases in CO 2 concentration. The mechanism of the response has proved elusive but here it is shown that density responses to both CO 2 concentration and humidity are correlated with changes in whole-plant transpiration and leaf abscisic acid (ABA) concentration.• The transpiration rate of a range of accessions of Arabido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 41 publications
7
110
1
4
Order By: Relevance
“…Although Holland and Richardson (2009) reported that stomatal density and guard cell length are both sensitive to environmental conditions and that considerable genotypic variation and phenotypic plasticity occurred in these traits, our study showed that differences among provenances in regards to guard cell length were not statistically significant, despite the decrease of L A in dry year for all provenances (Table 2). This is in agreement with the results presented by other authors, who found that stomatal density appears to be relatively plastic compared to stomatal length (Richardson et al 2001) and therefore, potentially adaptive to environmental change (Lake and Woodward 2008). Our study also showed that stomatal density increased with drought, which is consistent with the results obtained in some other plant species (Klooster and Palmer-Young 2004;Fraser et al 2009).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Although Holland and Richardson (2009) reported that stomatal density and guard cell length are both sensitive to environmental conditions and that considerable genotypic variation and phenotypic plasticity occurred in these traits, our study showed that differences among provenances in regards to guard cell length were not statistically significant, despite the decrease of L A in dry year for all provenances (Table 2). This is in agreement with the results presented by other authors, who found that stomatal density appears to be relatively plastic compared to stomatal length (Richardson et al 2001) and therefore, potentially adaptive to environmental change (Lake and Woodward 2008). Our study also showed that stomatal density increased with drought, which is consistent with the results obtained in some other plant species (Klooster and Palmer-Young 2004;Fraser et al 2009).…”
Section: Resultssupporting
confidence: 83%
“…Fraser et al (2009) also found that reduction of water supply in the field caused an increase in stomatal density, while the range in temperatures of approximately 2.8°C did not have significant effect on stomatal density. Likewise, study of Lake and Woodward (2008) evidenced that number of stomata increased in response to increasing VPD. Similarly, studying an impact of high and low vapor pressure deficit on leaf anatomical traits, Carins Murphy et al (2014) found that high VPD caused reduction of leaf area, whereas the leaf stomatal density increased.…”
Section: Resultsmentioning
confidence: 99%
“…Similar experiments have been preformed with air humidity, increased air humidity results in increased stomatal density (Sciutti and Morini, 1995). The stomatal density has been found to increase in plants with decreased ABA concentrations, which also have increased transpiration (Lake and Woodward, 2008). In Vicia faba drought and salinity stress has been found to increase the stomatal density and stomatal index, facilitating water uptake under water stressed conditions (Gan et al, 2010).…”
Section: Stomatal Development Under High Relative Air Humiditymentioning
confidence: 77%
“…In Arabidopsis thaliana it has been shown that ABA-deficient and ABA-insensitive mutants responded similarly as wild type plants to changes in humidity (Assmann et al, 2000). Plants developed under low ABA conditions also have higher stomatal density (Lake and Woodward, 2008), indicating that ABA is important in both the development of stomata size and density. ABA application in lower concentrations, applied to plants can reduce transpiration rate and increase the shelf life of Salvia splendens and a number of other ornamentals, by inducing stomatal closure (Pompodakis et al, 2004;Waterland et al, 2010a;Waterland et al, 2010b;Kim and van Iersel, 2011).…”
Section: Stomatal Development Under High Relative Air Humiditymentioning
confidence: 99%
“…In addition, we did not observe phenotypes indicative of compromised water transport, such as wilted leaves, in the cesa3 je5 mutants. Therefore, we propose that cellulose deficiency in cesa3 je5 mutants more directly causes an increase in stomatal aperture, whereas in cesa7 irx3-5 mutants, the smaller stomatal aperture brought about by decreased guard cell size might be due to collapsed xylem and compromised water transport , as fluctuations of supply and demand during water movement across the plant can modulate stomatal development (Lake and Woodward, 2008).…”
Section: Discussionmentioning
confidence: 99%